2018
DOI: 10.1142/s0219519418500112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Theory of Bone Mechanoregulation in the Physiological Loading Scenario

Abstract: In this paper, the theory of bone mechanoregulation under physiological loading was evaluated. The entire right tibiae of wild type (WT, [Formula: see text]) and parathyroid hormone (PTH, [Formula: see text]) treated C57BL/6J female mice were scanned using an in vivo [Formula: see text]CT imaging system at 14, 16, 17, 18, 19, 20, 21, and 22 weeks. The PTH intervention started from week 18 until week 22. Subject-specific finite element (FE) models were created from the [Formula: see text]CT images and physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Additionally, it was found that after the PTH treatment, the increasing TPA started from the midshaft region, while there is no clear pattern for the increasing TEA. One possible explanation for the adaptation pattern of TPA is that the midshaft region of the mouse tibia bears more weight than other regions of the mouse tibia during every day activities [ 32 ], which stimulates more bone formation activities, in agreement with the bone mechano-regulation mechanism [ 33 ]. Regarding the effect of PTH on the TEA, it is still unclear which parameter is the main one that regulates the increase of TEA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was found that after the PTH treatment, the increasing TPA started from the midshaft region, while there is no clear pattern for the increasing TEA. One possible explanation for the adaptation pattern of TPA is that the midshaft region of the mouse tibia bears more weight than other regions of the mouse tibia during every day activities [ 32 ], which stimulates more bone formation activities, in agreement with the bone mechano-regulation mechanism [ 33 ]. Regarding the effect of PTH on the TEA, it is still unclear which parameter is the main one that regulates the increase of TEA.…”
Section: Discussionmentioning
confidence: 99%
“…Bone length was measured from the pixel of the most tibial bone to the most distal bone. To account for the longitudinal growth (small in the considered age range, approximately 300 − 400 μ m [42]). We have considered 80% of the tibia length below the proximal growth plate.…”
Section: Discussionmentioning
confidence: 99%